2001
DOI: 10.1016/s1074-7613(01)00094-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Lymphotoxin-α to the Tumor Elicits an Efficient Immune Response Associated with Induction of Peripheral Lymphoid-like Tissue

Abstract: A recombinant antibody-lymphotoxin-alpha fusion protein induced an adaptive immune response protecting mice from melanoma. Importantly, this fusion protein elicited the formation of a lymphoid-like tissue in the tumor microenvironment containing L-selectin+ T cells and MHC class II+ antigen-presenting cells, as well as B and T cell aggregates. Furthermore, PNAd+/TCA4+ high endothelial venules were observed within the tumor, suggesting entry channels for naive T cell infiltrates. Over the course of therapy, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(103 citation statements)
references
References 37 publications
(1 reference statement)
4
97
0
Order By: Relevance
“…Through transfecting tumor cells with LIGHT, a cytokine capable of driving development of HEV in tumors, it has been shown that naïve transgenic T cells entering via these HEV can become primed within the tumor and contribute significantly to limiting tumor progression 25. Similarly, delivery of lymphotoxin‐α fused to tumor‐specific antibodies induces HEV development in B16 melanoma, resulting in infiltration and priming of effective antitumor T cells 26. In another study, adoptively transferred naïve transgenic T cells were shown to infiltrate tumors where they became activated and proliferated in response to antigens presented by cells within the tumor parenchyma 27.…”
Section: Discussionmentioning
confidence: 99%
“…Through transfecting tumor cells with LIGHT, a cytokine capable of driving development of HEV in tumors, it has been shown that naïve transgenic T cells entering via these HEV can become primed within the tumor and contribute significantly to limiting tumor progression 25. Similarly, delivery of lymphotoxin‐α fused to tumor‐specific antibodies induces HEV development in B16 melanoma, resulting in infiltration and priming of effective antitumor T cells 26. In another study, adoptively transferred naïve transgenic T cells were shown to infiltrate tumors where they became activated and proliferated in response to antigens presented by cells within the tumor parenchyma 27.…”
Section: Discussionmentioning
confidence: 99%
“…In primary and metastatic tumours, HEVs are associated with increased infiltration of naive, central memory and activated T cells that display a Th1 effector phenotype 66, 67, 70. A high density of extra‐tumoral and intra‐tumoral Th1 cells correspond with improved survival,71 where it is proposed that their local priming, possibly within ELFs, promotes antigen‐specific tumour responses 72, 73. In murine models of melanoma and lung carcinoma, the development of lymph node‐like vasculature allows naive T‐cell entry into tumours that delay tumour outgrowth 74.…”
Section: High Endothelial Venules At Elfsmentioning
confidence: 99%
“…In addition, this may stop lymphocytes from leaving the tumor microenvironment, which is beneficial since effective immunotherapy depends more on sustaining an immune response at the appropriate location than on its initiation [74]. Taken together, our results suggested that the effectiveness of tumor-targeted LT-a therapy was due to direct clonal expansion of tumor-specific T cells through the formation of peritumoral lymphoid tissue [69]. 16 Initial experiments designed to develop an autologous oral DNA vaccine protecting against murine melanoma indicated that peripheral tolerance toward melanoma selfantigens gp100 and TRP-2 could be broken by such a vaccine in CD57BL/6J mice.…”
Section: Tumor Targeting Of Lt-a Induces a Peripheral Lymphoid-like Tmentioning
confidence: 79%
“…Furthermore, our results suggested an improved T cell immune response, which is most likely evoked by the induction of peripheral lymphoid tissue at the tumor site. In fact, the functional significance of this tertiary lymphoid tissue at tumor sites was confirmed by immunohistologic and electron microscopic analysis of endothelial/lymphocyte interactions as well as TCR clonotype mapping, providing evidence for the induction of new T cell clones among tumor-infiltrating lymphocytes (TIL), which were shown to specifically lyse melanoma cells and to produce IFN-g in response to a TRP-2 180±188 -derived peptide [69].…”
Section: Tumor Targeting Of Lt-a Induces a Peripheral Lymphoid-like Tmentioning
confidence: 92%